Information Structure and its Interfaces - Mereu, Lunella (Interface Explorations [IE], 2009)
The volume presents recent results in the field of Information Structure based on research on Italian and Italian dialects, and on further studies on several typologically different languages. The central idea is that Information Structure is not an exclusive matter of syntax but an interface issue which involves the interplay of at least the phonological, morpho-syntactic and semantic-pragmatic levels of analysis. In addition, the volume is based on the study of actual language use and it adopts a cross-linguistic point of view.